Echocardiography and cardiac biomarkers in patients with non-small cell lung cancer treated with platinum-based chemotherapy - Omersa, Daniel (Radiol Oncol, 2016)
BACKGROUND: Non-small cell lung cancer (NSCLC) is the most common type of lung cancer and remains an important cause of cancer death worldwide. Platinum-based chemotherapy (PBC) for NSCLC can modify outcome while the risk of cardiotoxicity remains poorly researched. We aimed to evaluate the incidence and severity of cardiac injury during PBC in patients with NSCLC and to identify patients at risk. METHODS: This was a single-centre, prospective, observational study of patients with early and advanced stage NSCLC referred for PBC. In addition to standard care, patients were examined and evaluated for cardiotoxicity before the first dose (visit 1), at the last dose (visit 2) and 6 months after the last dose of PBC (visit 3). Cardiotoxicity (at visit 2 and 3) was defined as increase in the ultrasensitive troponin T, N-terminal pro-B type natriuretic peptide or decrease in left ventricular ejection fraction (LVEF). RESULTS: Overall, 41 patients (mean age 61 ± 9; 54% men; 68% advanced lung cancer) were included. The median number of PBC cycles was 4. During the study period, there were no incidents of heart failure, and 3 deaths caused by tumour progression were recorded. The mean values of biomarkers and LVEF did not change significantly (p > 0.20). However, 10 (25%) had cardiotoxicity which was independently associated with a history of ischemic heart disease (p = 0.026). CONCLUSIONS: In NSCLC, cardiac assessment and lifestyle modifications may be pursued in patients with a history of cardiac disease and in patients with longer life expectancy.